WAWASAN AL-QUR’AN TENTANG ANJURAN PERNIKAHAN - Nurnazli, Nurnazli (Universitas Islam Negeri Raden Intan Lampung, 2015)
One of the important teachings in Islam is themarriage. Marriage is a Sunnah of the Prophet andrecommended in Islam when someone has meetvarious requirements. The importance of the doctrineof marriage is that in the Qur'an there many verses,either directly or indirectly, addressed the issue ofmarriage. Marriage or paired an ordinance of Allah tohis creatures. It is repeatedly emphasized by Allah inthe Qur'an. Marriage in the Qur'an is a suggestion thata full requirements so that the goals of marriage ismentioned explicitly in the Qur'an, despite its generalnature. In the Qur'an there are two key words thatindicate the meaning of marriage, namely zawwaja andnakaha, which is in use, can be defined by marriage.The Qur'an uses these two words because it makes amarriage partner, conjugal relations lawfullyaccompanied by ijāb and qabūl.